The human capital as the production factor - Kucharčíková, Alžběta (Univerzita Pardubice, 2011)
Economic growth is the objective of economic policies in many countries.View of what constitutes major production factors and sources of economic growth,historically evolved. In the past, there existed the combined production of various production inputs in different types of human society. The article discusses the importance of human capital and learning as a form of investment in human capital in the formation of production functions and the achievement of extensive and intensive economic growth.
Keywords: human capital; economic growth; production factors; education